Pengaruh Pertimbangan Pasar Kerja, Pelatihan Profesional, Dan Personalitas Terhadap Minat Mahasiswa Akuntansi Pada Pemilihan Karir - Dananjaya, I Dewa Gde Ngurah; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 29 No 2 (2019)DO - 10.24843/EJA.2019.v29.i02.p30, 2019)
Careers are an important part of life. In choosing a career there are a number of considerations, namely consideration of the labor market, consideration of professional training and also recognition of personality. These three considerations form the basis of career selection where choosing a career is a major decision that impacts the future. Accounting students at the Faculty of Economics and Business, Udayana University, are the study population. Of the 217 respondents who had been determined through purposive sampling, only 182 respondents filled out the questionnaire. Data analysis in this study uses multiple linear regression analysis. The results found are that there is a positive influence between the variables of labor market considerations, professional training and personality on accounting students' interests in career selection. Keywords : Labor Market Considerations; Professional Training; Personality.